Implementation Of The Regulation Of The Minister Of Education And Culture Of The Republic Of Indonesia Number 1 Of 2021 At Smp Negeri 16 Bengkulu City - Sonata, Betaria; Yusuarsono, Yusuarsono; Handayani , Tuti (Journal of Law, Social Science, and Management Review, 2025)
This research aims to determine the implementation of the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 1 of 2021 concerning the New Student Admission System (PPDB) at SMP Negeri 16 Bengkulu City. The policy regulates the zoning system for new student admission which prioritizes students based on geographic proximity. This qualitative descriptive study involved interviews with school officials and parents, observation, and documentation. The study found that the implementation of the regulation at SMP Negeri 16 was conducted in an objective, transparent, and accountable manner. The zoning system was applied through an online application supported by the Education Office. Requirements and selection criteria were clearly communicated, primarily based on domicile verified by the family card. This system ensures educational equity by prioritizing local students and limiting favoritism toward certain schools. Informants confirmed the compliance of SMP Negeri 16 with the regulation and the clarity of its application procedures. Despite some challenges in public understanding, the school made efforts in disseminating information through social media and banners. The study concludes that SMP Negeri 16 has implemented the Ministerial Regulation effectively according to the zonation principles and has maintained public trust in the admission process.